Алмазному центру України – 45 років (фрагменти історії) - Колесниченко, Н.Ф. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The main stages of the 45-year history of V. N. Bakul Institute for Superhard Materials (ISM) of the National Academy of Sciences of Ukraine – the Diamond Center of Ukraine – the briefly outlined.